Light‐Induced Shape Morphing of Liquid Metal Nanodroplets Enabled by Polydopamine Coating. Issue 9 (16th January 2019) - Gan, Tiansheng; Shang, Wenhui; Handschuh‐Wang, Stephan; Zhou, Xuechang
Abstract: Shape morphing nanosystems have recently attracted much attention and a number of applications are developed, spanning from autonomous robotics to drug delivery. However, the fabrication of such nanosystems remains at an early stage owing to limited choices of strategies and materials. This work reports a facile method to fabricate liquid metal (LM) nanodroplets by sonication of bulk LM in an aqueous dopamine hydrochloride solution and their application in light‐induced shape morphing at the nanoscale. In this method, dopamine acts as a surfactant, which stabilizes the LM nanodroplets dispersion during the sonication, and results in downsizing of the nanodroplets. Furthermore, by adding 2‐amino‐2‐(hydroxymethyl)‐1, 3‐propanediol to the suspension, self‐polymerization of dopamine molecules occurs, resulting in the formation of polydopamine (PDA)‐coated LM nanodroplets. Owing to the high photothermal conversion of the PDA, PDA‐coated LM nanodroplets are transformed from spherical shapes to ellipsoids by NIR laser irradiation. This study paves a simple and reliable pathway for the preparation of functional LM nanodroplets and their application as shape‐morphing nanosystems. Abstract : Polydopamine (PDA)‐coated liquid metal (LM) nanodroplets are fabricated by sonicating bulk LM in an aqueous solution of dopamine hydrochloride and then triggering self‐polymerization of dopamine with 2‐amino‐2‐(hydroxymethyl)‐1, 3‐propanediol. When exposed to near‐infrared laser, spherical PDA‐coated LM nanodroplets are turned into ellipsoidal particles. This study paves a pathway for the preparation of functional LM nanodroplets and their application as shape‐morphing nanosystems.